CRIMES DE COLARINHO BRANCO: UMA ANÁLISE CRÍTICA DA SELETIVIDADE DO SISTEMA PENAL E A INCAPACIDADE DE ENFRENTAMENTO DAS ORGANIZAÇÕES CRIMINOSAS - ROSA, Gerson Faustino (2023)
This article has the general objective of a brief analysis of the relationship between criminal organizations and white-collar crimes, through criminology and the norms that underlie the current Brazilian legal system, related to the selectivity of the penal system when defining which conducts will be typified and on whom the penalties will apply, resulting in the frustration of the fight against economic crimes and their impunity. To achieve this scope, the object of the research was approached under the bibliographical analysis of legal, philosophical and sociological works, in addition to the study of paradigmatic cases.